2020 International Conference on Decision Aid Sciences and Application (DASA) 2020
DOI: 10.1109/dasa51403.2020.9317042
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning for Strategic Decision Making during COVID-19 at Higher Education Institutes

Abstract: Machine learning is becoming driving force for strategic decision making in higher educational institutions and it calls for cooperation between stakeholders and the use of efficient computation methods. Contrariwise, making decisions might consume much time, if there is no use of data and computational methods during the process of decision making.The utilization of machine learning is essential when coming up with an ultimate analysis of data and decision making. Besides, the technology which is under artifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
See 2 more Smart Citations
“…Table 4 summarizes the papers analysed, including information about the AI applied, who used the AI, and what main benefits it provided. In brief, the results revealed that the main advantages of AI applications in higher education were to improve educational outcomes [3,7,12,16,18,22,27,29,30,32], to enhance institutional decision-making [1,8,14,21,26], and to advance institutional systems [2,10,23]. Moreover, the end users benefiting from the AI applications mainly were higher education institutions (n=11), instructors (n=9), and college students (n=6).…”
Section: Advantages and Disadvantages Of Using Aimentioning
confidence: 99%
“…Improve educational decision-making processes, such as the admission process, curriculum, and learning activities [27] Regarding decision-making, paper [1] used different machine learning algorithms to advance data analysis at a higher education institute in Oman. Data from 1020 students were utilized to examine whether academic performance could predict the no-detriment rate.…”
Section: Higher Education Institutionsmentioning
confidence: 99%
See 1 more Smart Citation